Parasitoid wasps (Hymenoptera) from puparia of sarcosaprophagous flies (Diptera: Calliphoridae; Sarcophagidae) in Buenos Aires, Argentina Avispas parasitoides (Hymenoptera) a partir de puparios de moscas sarcosaprófagas (Diptera: Calliphoridae; Sarcophagidae) en Buenos Aires, Argentina - Adriana Oliva (Revista de la Sociedad Entomológica Argentina, 2008)
Emergence of parasitoid Hymenoptera from experimental rearings of sarcosaprophagous Diptera (Calliphoridae, Sarcophagidae) attracted to beef baits were recorded in Buenos Aires (Argentina) from 1998 to 2003. Four taxa were identified: Tachinaephagus zealandicus Ashmead (Encyrtidae), Brachymeria podagrica (Fabricius) (Chalcididae), Nasonia vitripennis (Walker) (Pteromaliidae) and Alysia sp. (Braconidae: Alysiinae). Only the first two species were abundant in all years. The number of added monthly emergences of each species is presented and correlated with monthly mean maximum-minimum temperatures. Se registró la emergencia de parasitoides (Hymenoptera) de crías experimentales de Diptera sarcosaprófagas (Calliphoridae, Sarcophagidae), atraídas a cebos de carne bovina, en Buenos Aires (Argentina) durante 1998-2003. Se determinaron cuatro taxones: Tachinaephagus zealandicus Ashmead (Encyrtidae), Brachymeria podagrica (Fabricius) (Chalcididae), Nasonia vitripennis (Walker) (Pteromaliidae) y Alysia sp. (Braconidae: Alysiinae). Sólo las dos primeras especies resultaron abundantes en todos los años. Se ha graficado el número total de emergencias de cada especie para cada mes, junto con las temperaturas promedio máxima y mínima.